Assessment of Cucumber Genotypes for Salt Tolerance Based on Germination and Physiological Indices. Issue 4 (21st November 2019) - Marium, Asma; Kausar, Abida; Ali Shah, Syed Muhammad; Ashraf, Muhammad Yasin; Akhtar, Noreen; Akram, Muhammad; Riaz, Muhammad
Soil salinity is one of the primary problem for agricultural crops which causes a great loss in crop production in Pakistan and worldwide. Various approaches have been implemented to overcome salinity problem. Assembly of crops for the enhancement of salt tolerance is a good strategy to achieve cost-effective yields. Cucumber is considered as one of the leading vegetable crop around the world for the nourishment of human being as source of nutrients, minerals, and vitamins. Screening of 12 cucumber genotypes using some physiological indices, that is, seedling germination stress tolerance index, plant height stress tolerance index, root length stress tolerance index, shoot and root dry weight stress tolerance index, and shoot and root fresh weight stress tolerance index were performed for the identification of salt tolerance. Using the above characteristics genotypes, Valley and HC-999 were categorized as tolerant, Safaa and Debra as medium tolerant, while Thamin-II identified as medium sensitive and NSC-CM1 and Akbar are classified as sensitive genotypes of cucumber. According to the current study findings, the screened cucumber genotypes for salinity tolerance can also be suggested to farmers for the improved production and yield of crop at saline soil.